Generative AI, Disruptive Innovation, and Marketing Firm Strategies: Opportunities and Implications - AbouElgheit, Emad (International Journal of Applied Research in Management and Economics, 2024)
This study investigates the potential of small marketing firms to disrupt the market by adopting generative AI technology and the theory of disruptive innovation. The study employs a qualitative approach, combining a comprehensive literature review with in-depth interviews with leaders of small marketing firms. The research findings position generative and conversational AI as the next technological evolution, succeeding the internet and mobile/social era. It is the first study applying the theory of disruptive innovation to generative AI use in small marketing firms, presenting a positive outlook toward integrating generative AI into marketing operations. The study contributes to the emerging knowledge of AI in marketing, offering practical implications for scholars and practitioners to advance this field.